Localization of protective epitopes of the amino terminus of type 5 streptococcal M protein (The Rockefeller University Press, 1986)
We have used a set of overlapping chemically synthesized peptides representing the amino terminus of type 5 streptococcal M protein to localize protective, as opposed to nonprotective and tissue- crossreactive epitopes that might be appropriate for vaccine formulations. Rabbit antisera raised against SM5(1-35) reacted in high titer with pep M5 by ELISA and opsonized type 5 streptococci. None of the antisera crossreacted with human heart tissue or myosin. Antisera against SM5(26-35) reacted with SM5(1-35) and pep M5 but failed to opsonize type 5 streptococci. Particle-phase ELISA indicated that SM5(26-35) antibodies were directed against nonprotective determinants of pep M5 that were not exposed on the surface of viable organisms. Opsonization and ELISA inhibition assays showed that, of the SM5(1-35) antibodies that reacted with M5, all were inhibited by SM5(14-35), whereas none was inhibited by SM5(26-35), suggesting that the protective epitopes of SM5(1-35) resided between residues 14 and 26. This was confirmed by subsequent chemical synthesis of this region; SM5(14-26) totally inhibited SM5(1-35) antibodies that reacted with pep M5 in ELISA, and completely inhibited opsonization of type 5 streptococci by SM5(1-35) antibodies. SM5(14-26) evoked high titers of type-specific, opsonic antibodies against type 5 streptococci, confirming the protective immunogenicity of this 13-residue peptide of type 5 M protein.